(untitled) - 1981-; Stiefvater, Maggie (New York, 2014)
Cole St. Clair has come to California for one reason: to get back Isabel Culpeper.
Keywords: Metamorphosis; Fiction; Wolves; Fiction; Human-animal relationships; Fiction; Fiction; Juvenile fiction; Paranormal fiction; Juvenile fiction; Wolves; Human-animal relationships; Juvenile fiction; Metamorphosis; Supernatural; California; California; Juvenile fiction; Fiction